Tenaga Nasional Berhad - Case Study Approach - Mat Noh, Mohamad Jeffri (2006)
Tenaga Nasional Berhad (TNB) is the dominant electric utility in Malaysia. TNB owns roughly sixty percent of all peninsular Malaysia\'s generation assets and roughly fifty percent of all Malaysian generation through its generation subsidiaries and holds a monopoly over transmission and distribution in all of Peninsular Malaysia.